ANTITHROMBOTIC ACTIVITY OF SBT-828 COMPOUND - V. S. Sirotenko; M. Туan (Фармация и фармакология (Пятигорск), 2015)
We have studied antiplatelet activity of new indole derivants on the experimental model of ADP induced aggregation of platelets in rabbit's plasma in vitro. Seven of the studied substances exceeded comparing drug of acetylsalicylic acid on EK50